Fusarium oxysporum f. sp. cepae, the causal agent of Fusarium basal rot of onion: biology, epidemiology and management - Swift, Curtis E., author; Brown, William M., advisor; Schwartz, Howard F., advisor; Bartolo, Michael E., committee member; Cranshaw, Whitney S., committee member (Colorado State University. Libraries, 2001)
The bulb onion (Allium cepae L.) is an important food crop having been used for over 5000 years. Fusarium oxysporum Schlecht. f. sp. cepae (Hanzawa) Snyder & Hansen (F. o. cepae), the causal agent of Fusarium basal rot of onion bulbs, is present in most parts of the world where onions are grown and is a major disease problem of this crop. This pathogen causes up to 90% loss of seedlings, and 30% loss of stored bulbs. This dissertation reports research conducted on the biology, epidemiology and management of Fusarium oxysporum f. sp. cepae in Colorado. Three Vegetatively Compatible Groups of Fusarium oxysporum f. sp. cepae were identified in Colorado. One VCG has a wide ranging presence in Colorado, one is restricted to Delta County, and the third is present in Mesa County. Two additional VCGs identified are single isolate VCGs. Up to one hundred and thirty cfu's of Fusarium were present in each milliliter of irrigation water. Fusarium contaminated irrigation water can infest fields previously free of F. o. cepae. Care must be taken to prevent tailwater from infested fields from entering irrigation water supplies. Total Fusarium and F. o. cepae populations varied between year and location in Fusarium contaminated fields. Propagule numbers were greatest in fields planted to onions than fields planted to pinto beans. Total Fusarium populations was as high as 7900 cfu's gram-1 of native soil. Greenhouse trials of metalaxyl, imazalil, fosetyl-aluminum/iprodione, and thiophanate methyl, resulted in significantly fewer living plants than untreated checks. This may have been due to phytotoxic effects of these materials when applied to steam-sterilized soil. Seedling emergence was significantly greater with metam-sodium treatments than other treatments evaluated. There was no significant difference between band-applied rates of 280.7 and 327.4 liters hectare-1. Post-emergence treatments of thiophanate-methyl, metalaxyl, and fosetyl-aluminum/iprodione are ineffective in reducing Fusarium basal rot or increasing yield. Metam-sodium, band-applied at 223.8 and 280.7 liters hectare-1, and broadcast-applied at 701 liters hectare-1, resulted in significant increased yields of marketable onions. Metalaxyl consistently resulted in reduced marketable yields due to reduced emergence and seedling survival.
Keywords: plant pathology